Gender Differences in Psycho-Social-Spiritual Healing - Luna, María José (J Womens Health (Larchmt), 2019)
Background: Many individuals exhibit significant distress in response to serious and/or life-limiting illness. However, there are others who make life-transforming changes, which involve healing experiences in the psychological, social, and spiritual domains of life regardless of illness outcome. The aim of the present study is to determine if there are any differences in psycho-social-spiritual healing between genders. Materials and Methods: The NIH Healing Experiences in All Life Stressors (NIH-HEALS), a 35-item measure of psycho-social-spiritual healing, is composed of three factors: Connection, Reflection & Introspection, and Trust & Acceptance. NIH-HEALS and a demographic questionnaire were administered to 193 patients with serious and/or life-limiting illness at the National Institutes of Health Clinical Center. Results: In response to NIH-HEALS, men and women significantly differed on the Reflection & Introspection factor. Women reported increased enjoyment of mind–body practices (p < 0.001), compassion (p = 0.005), gratitude (p = 0.014), and a desire to be more positive (p = 0.044) compared to men. Men rated their pain levels (p = 0.035) and severity of illness (p = 0.016) higher and their overall level of health (p = 0.010) poorer compared to women. Women's responses to items regarding compassion (r(s) = 0.37, p < 0.001) and gratitude (r(s) = 0.24, p = 0.015) correlated positively with better overall health ratings. Conclusion: Men and women show some differences in their self-reported psycho-social-spiritual healing, which may have implications when designing interventions aimed at promoting a healing experience in the context of serious and life-limiting illness.